SDSS-IV MaNGA: stellar population gradients as a function of galaxy environment - Goddard, D.; Thomas, D.; Maraston, C.; Westfall, K.; Etherington, J.; Riffel, R.; Mallmann, N.D.; Zheng, Z.; Argudo-Fernández, M.; Bershady, M.; Bundy, K.; Drory, N.; et al. (Oxford University Press, 2017)
We study the internal radial gradients of stellar population properties within 1.5 Re and analyse the impact of galaxy environment. We use a representative sample of 721 galaxies with masses ranging between 109 M⊙ and 1011.5 M⊙ from the SDSS-IV survey MaNGA. We split this sample by morphology into early-type and late-type galaxies. Using the full spectral fitting code firefly, we derive the light and mass-weighted stellar population properties, age and metallicity, and calculate the gradients of these properties. We use three independent methods to quantify galaxy environment, namely the Nth nearest neighbour, the tidal strength parameter Q and distinguish between central and satellite galaxies. In our analysis, we find that early-type galaxies generally exhibit shallow light-weighted age gradients in agreement with the literature and mass-weighted median age gradients tend to be slightly positive. Late-type galaxies, instead, have negative light-weighted age gradients. We detect negative metallicity gradients in both early- and late-type galaxies that correlate with galaxy mass, with the gradients being steeper and the correlation with mass being stronger in late-types. We find, however, that stellar population gradients, for both morphological classifications, have no significant correlation with galaxy environment for all three characterizations of environment. Our results suggest that galaxy mass is the main driver of stellar population gradients in both early and late-type galaxies, and any environmental dependence, if present at all, must be very subtle.